The accuracy of Aziza’s scoring system in limited slice non-enhanced thoracic CT for the diagnosis of adult pulmonary tuberculosis (Faculty of Medicine Universitas Indonesia, 2017)
Background: Tuberculosis (TB) is still a major cause of morbidity and mortality in Indonesia. Thus, a fast and accurate method in diagnosing pulmonary TB (PTB) is needed, especially in adult smear-negative-TB cases. The purpose of this study was to determine the accuracy of a novel scoring system (Aziza’s score) using clinical data and characteristic abnormalities that are found in the limited slice non-enhanced thoracic CT. Methods: This was a prospective cross-sectional study. A limited slice non-enhanced thoracic CT was performed to establish a diagnosis of PTB in patients with suspected PTB and to assess the diagnostic value of the scoring system. A reference standard used in this study was the clinical expertise of two pulmonologists. The scoring system was analyzed using bivariate and multivariate Cox regression analysis. Results: 84 of 130 suspected PTB patients were diagnosed as PTB. They were diagnosed based on pulmonary characteristic abnormalities that were found in the limited slice non-enhanced thoracic CT. The scoring system was analyzed using bivariate and multivariate Cox regression analysis. The total scores which were equal to or more than 29 could diagnose PTB with the accuracy of 96.1% (95% CIs=91.3–98.3), sensitivity of 96.5% (95% CIs=90.1–98.8), and specificity of 95.6% (95% CIs=90.1–98.8), This novel scoring method was name as an Aziza’s scoring system. Conclusion: Aziza’s scoring system performed in the limited slice non-enhanced thoracic CT has a higher accuracy compared to the reference standard for the diagnosis of adult PTB.